Islamic Boarding School (IBS) Business Incubator: A Model of The Economic Development and Empowerment of Islamic Boarding Schools (IBS) in NTB - Intan Kusuma Pratiwi; Shofia Mauizotun Hasanah (International Journal of Islamic and Social Sciences (ISOS), 2021)
West Nusa Tenggara has quite a number of Islamic boarding schools, which are 549. Islamic boarding schools can be developed into a people's economic base and economic development centers for the people in the regions, either in the form of Islamic financial institutions (Islamic boarding schools/kopontren) or other real business fields according to with assets owned by the pesantren. To facilitate this, an incubator for work skills and an entrepreneur/ business incubator is present. This research was carried out using a qualitative approach with the type of literature study research by looking for theoretical references that are relevant to the cases or problems found. The business incubator is one of the strategies to create new entrepreneurs. A business incubator is a support service for creating and developing new businesses that have high economic value and competitiveness. Business incubators are considered capable of optimizing the use of humanresources, and providing other facilities such as funding, working space, networking as well as providing technical and management training in the services they provide.